Forced Nonlinear Vibrations in a Smart Magneto-Viscoelastic Multiscale Composite Nanobeam in a Humid Thermal Environment - Lakshmanan ANITHA; Loganathan RAJALAKSHMI; Rajendran SELVAMANI; Farzad EBRAHIMI (Engineering Transactions, 2023)
In this paper, we study forced harmonic waves in a magneto-electro-viscoelastic (MEV) nanobeam embedded in a viscoelastic foundation using nonlocal strain gradient elasticity theory. The viscoelastic foundation is modeled as a Winkler-Pasternak layer. The governing equations of the nonlocal strain gradient viscoelastic nanobeam are derived using Hamilton’s principle and solved analytically. A parametric study is presented to examine the effects of physical variables on the field. It is found that the effect of strain gradient and nonlocal parameter on dimensionless amplitude and phase angle is quite important. The findings from this study highlight the significance of identifying magneto-piezoelectricity in predicting the vibration characteristics of intelligent nanostructures and elucidating the impact of humid thermal effects on nanomaterials.